Efektivitas Pembelajaran Aspek Kognitif Melalui Penerapan Kuis-Nht Pada Siswa Kelas Xa SMA Negeri 12 Pekanbaru - M Nor; Suarji Suarji; Hendar Sudrajad (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2010)
This study aimed to examine the effectiveness cognitive aspects of learning through the implementation theNHT Quiz-XA grade students at SMAN 12 Pekanbaru on subject matter the electrical circuit and KirchoffLaw in the academic year 2008/2009. The subjects were students of class XA 12 Pekanbaru SMA 2008/2009school year which amounted to 41 students. Data collection instrument is flat assessment of cognitiveachievement test. Data were analyzed using descriptive analysis techniques, including aspects relevant to thesubject matter and the characteristic of students. Results of data analysis shows that subject matter masteryof 91.7% with a complete mastery category by category relevance is very high and classical mastery learningstudents is 87.8% with a category of exhaustiveness is finished with high relevance category, learningeffectiveness of students categorized as effective.